1993
DOI: 10.1210/jcem.77.5.8077309
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of umbilical cord plasma corticotropin-releasing hormone in growth-retarded fetuses.

Abstract: CRH is synthesized in the hypothalamus and released in response to stress into the portal hypophyseal blood; an additional site of synthesis, the placenta, is present only during pregnancy. Placental CRH is released into the maternal and fetal circulation during human pregnancy, and we hypothesized that the chronic fetal stress associated with fetal growth retardation may stimulate placental CRH release. We measured plasma CRH concentrations in the umbilical cord blood of 28 growth-retarded fetuses and 28 norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 2 publications
0
70
0
Order By: Relevance
“…Most studies have found that maternal stress affects birth weight by shortening gestational age (Copper et al 1996;Nordentoft et al 1996). However, some support exists for an effect on intrauterine growth restriction (IUGR; Wadhwa et al 2004), probably driven by higher levels of placental CRH resulting in decreased uteroplacental flow and hypoxemia, which are known risk factors for IUGR (Giles et al 1996;Goland et al 1993).…”
Section: Maternal Stress and Birth Weight: Accounting For Mechanismsmentioning
confidence: 99%
“…Most studies have found that maternal stress affects birth weight by shortening gestational age (Copper et al 1996;Nordentoft et al 1996). However, some support exists for an effect on intrauterine growth restriction (IUGR; Wadhwa et al 2004), probably driven by higher levels of placental CRH resulting in decreased uteroplacental flow and hypoxemia, which are known risk factors for IUGR (Giles et al 1996;Goland et al 1993).…”
Section: Maternal Stress and Birth Weight: Accounting For Mechanismsmentioning
confidence: 99%
“…In the human fetus, significant alterations occur in HPA function in pregnancies complicated by maternal undernutrition (Warnes et al 1998), maternal alcohol consumption (Wilcoxon et al 2003), maternal infection (Gravett et al 2000), fetal asphyixia (Procianoy et al 1988), intra-uterine growth restriction (Goland et al 1993) and pre-eclampsia (Procianoy and Cecin 1986). These changes in HPA function are predominantly defined by an increase in cord blood cortisol and a decrease in cord blood dihydroepiandrosterone sulphate (DHEAS).…”
Section: Hpa Functionmentioning
confidence: 99%
“…However, the maternal cortisol that still crosses the placenta represents 25-50% of the plasma cortisol in the fetus, and therefore high levels of maternal glucocorticoids, exceeding the limit of placental 11 ␤-hydroxysteroid dehydrogenase, or pathological conditions impairing placental functions might lead to fetal exposure to excess glucocorticoids (5). In humans fetal cortisol levels are increased during fetal growth retardation (6,7), a situation that often is associated to impaired placental function (8). Prenatal excess of glucocorticoids modifies the development of several organs, including the lung, heart, gut, and kidney (9,10).…”
mentioning
confidence: 99%